Extraterrestrial minerals and future frontiers in mineral exploration (2013)
Due to the high rates of consumption of minerals and the high human population growth, mineral resources on planet Earth are in the process of exhaustion, this shortage creates the need to fi nd new alternatives to supply the growing needs. An additional alternative to the traditional search for new deposits on Earth, is the search for deposits beyond our planet, these new resources can be found in the vicinity of our planet. The mining of bodies of our solar system like the Moon, Mars and the asteroid belt can provide abundant energy resources such as helium 3 and minerals such as potassium, rare earth elements, iron and platinum group minerals. Now some companies are planning this exploration and for geologists and mining professionals in general, it has considerable potential for scientifi c research, technological innovation and professional development in new fi elds.